An analysis of the branch-and-bound method in solving the reactive optimal power flow problem - Matos, Luiza [UNESP]; Silva, Daisy [UNESP]; Soler, Edilaine [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
The purpose of an Optimal Power Flow (OPF) problem is to determine the state of an electric power transmission system that optimizes a given system performance and satisfies its physical and operational constraints. The OPF problem can be mathematically modeled as a nonlinear programming problem with discrete and continuous variables. In this paper, we investigate the efficiency of the Branch-and-Bound method in solving the OPF problem considering its continuous and discrete variables. In order to, three different solutions algorithms involving this method are analyzed. Numerical tests with the IEEE 14, 30, 118 and 300 buses electrical systems are presented.